2011
DOI: 10.1310/hpj4601-26
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Alvimopan Use as Part of Perioperative Management of Patients Undergoing Laparoscopic Small and Large Bowel Resections

Abstract: Objective: Delayed gastrointestinal (GI) recovery (postoperative ileus) is a risk for patients undergoing bowel resection (BR) and presents clinical challenges including prolonged hospital length of stay (LOS) and increased postoperative morbidity. Alvimopan, an oral, peripherally acting mu-opioid receptor antagonist, is the first therapy approved to accelerate GI recovery after BR. Published data have described alvimopan use in open BR. In contrast, this study focused on laparoscopic BR. Methods: Historic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 38 Finally, hospital cost data were not collected in our study. However, in a recently published study 33 of alvimopan use in laparoscopic bowel resection at a regional medical center, a 1.1 day reduction of LOS was associated with a hospital cost savings of $1,368 (this included alvimopan costs). Therefore, it is likely that, based on a day and a half reduction in LOS, cost savings will be realized at our institution as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 Finally, hospital cost data were not collected in our study. However, in a recently published study 33 of alvimopan use in laparoscopic bowel resection at a regional medical center, a 1.1 day reduction of LOS was associated with a hospital cost savings of $1,368 (this included alvimopan costs). Therefore, it is likely that, based on a day and a half reduction in LOS, cost savings will be realized at our institution as well.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Indeed, some recently published single-institution/system studies have indicated a potential benefit for alvimopan in patients undergoing laparoscopic bowel resection. 33 , 34 Therefore, based on the drug's mode of action, we propose that in patients for whom opioid-based analgesia was used, alvimopan may help accelerate patient GI recovery; thereby shortening their hospital stay. We designed a retrospective chart review to study the effect of adding alvimopan to a standard perioperative recovery pathway used for elective laparoscopic partial colectomies.…”
Section: Introductionmentioning
confidence: 99%